2003
DOI: 10.1007/bf03166636
|View full text |Cite
|
Sign up to set email alerts
|

ESR parameters of a series of La@C n isomers

Abstract: Abstraer.A systematic characterization of a series of La@C, by temperature-dependent electron spin resonance (ESR) in solution was performed. The anisotropic ESR parameters of the g-factor, the hyperfine coupling tensor, and nuclear quadrupole interaction were determined by a quantitative analysis of the linewidth on the basis of the hydrodynamics in solution. Asa result, it was found that the electronic structure of all La@C, was stabilized by an intramolecular charge transfer and can be described as La3+@C 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 22 publications
2
11
0
Order By: Relevance
“…Akasaka and co‐workers published the first isolation and characterization of this minor isomer of La@C 82 with a hfcc of 0.836 G, corresponding to C s symmetry . Isomers of La@C 2n (2n = 76 − 90) studied by ESR spectroscopy exhibited similar features to those reported previously, with small hfcc and g values centered around 2.003 . ESR studies of pure samples of Sc@C 82 (C 2v , C s ) and Sc@C 84 were reported by Shinohara in 2000.…”
Section: Endohedral Fullerenessupporting
confidence: 58%
“…Akasaka and co‐workers published the first isolation and characterization of this minor isomer of La@C 82 with a hfcc of 0.836 G, corresponding to C s symmetry . Isomers of La@C 2n (2n = 76 − 90) studied by ESR spectroscopy exhibited similar features to those reported previously, with small hfcc and g values centered around 2.003 . ESR studies of pure samples of Sc@C 82 (C 2v , C s ) and Sc@C 84 were reported by Shinohara in 2000.…”
Section: Endohedral Fullerenessupporting
confidence: 58%
“…The EPR spectrum of La@C 72 (Figure a) shows eight clear splitting peaks; the isotropic hyperfine coupling constant of a­(La) iso is 0.16 G, and the g-factor is 2.0018. Among reported mono La-based metallofullerenes, this a­(La) iso value is the smallest one, and the g value is similar to those of La@C 82 derivatives and La@C 86 –II . The EPR spectrum of Y@C 72 (Figure b) shows two clear splitting peaks; the isotropic hyperfine coupling constant of a­(Y) iso is 1.75 G, and the g-factor is 2.0015.…”
Section: Resultssupporting
confidence: 84%
“…After soxhlet extraction, a highly purified sample of the major isomer of Gd@C 82 Gd@C 82 (I) (C 2v ) was obtained by employing high performance liquid chromatography (HPLC) as described in a previous report (1). After soxhlet extraction, a highly purified sample of the major isomer of Gd@C 82 Gd@C 82 (I) (C 2v ) was obtained by employing high performance liquid chromatography (HPLC) as described in a previous report (1).…”
Section: Methodsmentioning
confidence: 99%